Carbapenem resistant Acinetobacter Species infection in intensive care unit: The outcome and risk factors of mortality - Wan Hassan, Wan Mohd Nazaruddin; Puzizer, Mohd Samsul; Deris, Zakuan Zaini; Mohamed Zaini, Rhendra Hardy (Bangladesh Journal of Medical Science, 2019)
Objective: Acinetobacter spp. infection is a challenging problem in intensive care unit (ICU) because of its multi-drug resistant (MDR) in nature to antibiotic therapy including broadspectrum carbapenem group. The aims of the study were to determine the risk factors of mortality and the outcome of carbapenem-resistant Acinetobacter spp. (CRAs) infection in our ICU. Materials and Method: This is a retrospective, cross-sectional study, done in 2 years from January 2008 to December 2009. The list of the patients was obtained from hospital nosocomial infection surveillance unit and ICU infection record. The data of the patients were subsequently reviewed from their respective medical records after approval from university ethics committee and hospital medical record unit. Results and Discussion: A total of 92 patients were reviewed and only 54 were included and analyzed. The prevalence of CRAs over 24 months was 7.3%. Mortality was 50% among the reviewed patients and this contributed 13.6 % of the total ICU mortality. Age was significantly different between survival and non-survival groups; 43.07 (21.09) vs. 57.04 ± 14.33 year old (p = 0.006). Age was also the only significant independent risk factor associated with mortality in CRAs (adjusted OR = 1.045, 95% CI: 1.010, 1.081, p = 0.011). There were no other significant risk factors. The length of ICU stay was 17.00 (13.58) days whereas length of hospital stay was 41.37 (27.66) days in survival group. Conclusion: CRAs caused 13.6% of total ICU mortality and older age group was the independent risk factor for mortality. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.98-104